Le Poisson-Avaleur - Clément, Daniel (Anthropologica, 2022)
This article deals with the Poisson-avaleur, a mythical episode which has already been analyzed by some structuralists and which is interpreted as the birth of a human being, an interpretation which cannot be supported by some of its elements. In fact, this mythical episode is based on two kinds of natural phenomena: a feeding habit of the fishes identified as the poisson-avaleur and stories of giant fishes that circulate at least in one area where the myth is told. The discovery of the narrative etymons further helps us to unfold the primary and secondary teachings of the episode. The result of this analysis of the Poisson-avaleur questions Saussure's doctrine of the arbitrary character of the sign on which is based the structural analysis of myth. It also illuminates the specific nature of myth in which, on the contrary, the relation between the components (signifier) and reality (signified) is not arbitrary. Finally, our critique of structuralism is akin to that of Giddens (1979) who argues that social practice and the actor's knowledge are fundamental for understanding social phenomena.